The Liturgy of Life: Alexander Schmemann - Plekon, Michael (Religions, 2016)
The émigré Russian priest and theologian Alexander Schmemann (1921-1983) spent most of his career as a faculty member and dean of St. Vladimir's Orthodox Seminary in Crestwood, New York, not far from New York City. For over 30 years, in lectures, teaching and numerous publications, he presented the distinctive vision of the Eastern Church, mostly unknown to Western Christians, in which the church's liturgy was the primary source not only of its theology but of all other aspects of its life. I offer an overview of his work, with analysis and criticism and an assessment of his continuing significance.